2012
DOI: 10.3928/15428877-20120102-06
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Morning and Evening Choroidal Thickness in Japanese Subjects With No Chorioretinal Disease

Abstract: The choroidal thickness varies according to the time of measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
2
17
3
Order By: Relevance
“…Tan et al [19] reported a mean CT of 372.2  μ m measured by SD-OCT in a younger age group, but the RE was similar. Toyokawa et al [22] reported a mean CT of 308.5  μ m, similar to our study, but the mean age was older (62.6 years). In the study by Ikuno et al [14], the mean choroidal thickness was 354  μ m by 1060 nm HP-OCT, the patients had a wider range of age (23–88 years old), and the mean RE was −1.9 ± 2.3 D. Our results were higher than the 287 ± 76  μ m measured with Heidelberg SD-OCT in a study of thirty-four healthy American subjects that was reported Margolis and Spaide [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tan et al [19] reported a mean CT of 372.2  μ m measured by SD-OCT in a younger age group, but the RE was similar. Toyokawa et al [22] reported a mean CT of 308.5  μ m, similar to our study, but the mean age was older (62.6 years). In the study by Ikuno et al [14], the mean choroidal thickness was 354  μ m by 1060 nm HP-OCT, the patients had a wider range of age (23–88 years old), and the mean RE was −1.9 ± 2.3 D. Our results were higher than the 287 ± 76  μ m measured with Heidelberg SD-OCT in a study of thirty-four healthy American subjects that was reported Margolis and Spaide [13].…”
Section: Discussionsupporting
confidence: 90%
“…However, the study population is younger than ours and the mean baseline CT is thicker. Toyokawa et al [22] reported a significant diurnal variation of 20  μ m, with the thickest being in the evening, although the baseline choroidal thickness is the same and the study population was older than ours. In studies by Usui et al [18] and Tan et al [19], the mean choroidal thickness decreased during day while Chakraborty et al [24] and Toyokawa et al's [22] population showed an increase.…”
Section: Discussioncontrasting
confidence: 58%
“…35 Moreover, subfoveal CT is, on average, 62 mm higher in men than women 35 and has a circadian variation, being slightly thicker at the end of the day. 36,37 Existing studies did not find a clear relationship between CT and systemic arterial blood pressure. 37,38 Recently, we have witnessed a growing interest for the study of the choroid in various retinal, choroidal, or optic nerve pathologies.…”
Section: Discussionmentioning
confidence: 98%
“…We did not have information on carotid artery stenosis for our CAD or control groups. In addition, because we recruited patients with CAD during the afternoon clinic and control patients during both the morning and afternoon clinic, we were unable to control for diurnal variation in CTh, which is thought to be 20–30 μm from morning to evening [5052]. However, on further analysis of our imaging timings, the average difference between time of imaging of CAD compared to controls was approximately 2 hours, which would equate to a 5 μm or less difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%